Global Existence of Periodic Solutions in a Delayed Kaldor-Kalecki Model - Kaddar, A.; Talibi Alaoui, H. (Nonlinear Analysis: Modelling and Control, 2009)
This paper is concerned with a delayed Kaldor-Kalecki non-linear business cycle model in income. By applying a global Hopf bifurcation result due to Wu, the global existence of periodic solutions is investigated. Numerical examples will be given in the end, to illustrate our theoretical results.